Characteristics of the fracture geometry and the injection pressure response during near-wellbore diverting fracturing. (November 2021) - Wang, Bo; Zhou, Fujian; Zhou, Hang; Ge, Hui; Li, Lizhe
Abstract: Near-wellbore diverting fracturing (NWDF) can successfully generate new diverting fractures and dramatically enhance the stimulation effects for vertical wells. Investigating the fracture geometry and the injection pressure response is necessary for the candidate well selection and the stimulation effect evaluation. This work establishes a fully fluid–solid coupling model to simulate the process of NWDF under various parameter combinations, including the horizontal stress contrast, Young's modulus, rock tensile strength, rock permeability, pore pressure, and injection rate. The model is verified against the reported experimental results. Moreover, the following key methods were applied in this study. Extended finite element method (XFEM) is applied to simulate the arbitrary fracture propagation path, which is a mesh-free simulation method; the initiation and propagation of the fracture tip elements are characterized by the cohesive zone model; a truss model is applied to simulate the propping effects of the proppants; a plug model is proposed to simulate the plugging effects of the tight plug. The simulation results show that the stimulation effects of NWDF can be improved by selecting the candidate well of low horizontal stress contrast, low Young's modulus, low rock permeability, high rock tensile strength. However, the pore pressure has no impact on the stimulation effects of NWDF. Enhancing the fluid injection rate can improve the stimulation effects while the injection rate should be optimized for certain well. During the field operation of NWDF, a large difference between the peak value and the steady value of the diverting fracture injection pressure denotes a large curvature of the diverting fracture and a bad stimulation result. No obvious peak value of the diverting fracture injection pressure denotes a straight diverting fracture and a perfect stimulation result.